(3GdCLhHI GdaGNQI Ydi GdCSFdI GdaGLQIs - (3GdUfgGLj GdnbnQGaj, CHh GdYHGS, TgGH GdOjf, CMeO Hf EOQjS Hf YHO GdQMef, J (B684 (3g`s ((3YHOg eMeO fLjH Hf gdGd GdOjf GdCdLGfjs)
(3ChdgG (B:s
(3HYO GdHSedI ; bGd GdTjN GdEeGe GMeO Hf EOQjS GdeGdcj GdeYQha HGdbQGaj GeG HYO aEf HYV GdfUGQi CfTC QSGdI Ydi dSGf GdfUGQi eTjQG Cf ZjQg gh GdbGjd hGfg gh GdSGFd s
(3BNQgG (B:s
(3adG JLO ddMb aj bdhHge eMdG hdG dSeGY GdJPcQI GgdG hGddg JYGdi gh GdeMehO hHeG jdjb HLdGdg GdPj LYdfG eNUhUjf HOjfg Gdbhje hUQGWg GdeSJbje hgh MSHfG hfYe Gdhcjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 94s
(3eYLe GdeDdajf (B1 / 100s
(3cTa GdXfhf (B1 / 11s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds